Hybridity in Public Sector Universities: A Comparative Analysis of influences in Finland and the Netherlands - van Vulpen, Nina Jorien (My University, 2015)
Hybridity is a concept that is increasingly visible in public sector management including universities across Europe. Hybridity has been recognized as an alternative to full marketization of higher education. The current thesis addresses the drivers of hybridity, as well as their influences on structures and governance of public sector universities in two European countries i.e. Finland and the Netherlands. The conceptual part of the thesis developed a framework for comparative analysis of both countries. Key drivers for hybridity in universities are defined from public sector to be global influences, European Union and national reforms, while from private sector, the drivers include best practices, role of stakeholders and job market. The influences of these factors on hybrid universities is visible in aspects of structure (ownership and funding) and governance (values and autonomy). The country specific analysis revealed that both Finland and the Netherlands were traditional European welfare states, where reforms due to NPM, as well as changes in global and regional context has led to implementation of hybridity in university structures and governance. The thesis found differences in both countries in this context. The reform process started earlier in the Netherlands compared to Finland, and hybridity’s influences are more visible in Dutch universities’ structures and governance. The comparative analysis found that still universities’ physical ownership is in public hands, though financial ownership increasingly includes private sector especially in Dutch universities. The thesis also found that public sector funding is still major source for universities in both countries, though in Dutch case, the share of private sector is more visible now. It was further found that Finnish universities still represent more public values as depicted by free access to higher education, while Dutch universities increasingly represent private values as depicted by fees for local students and commercialized approach to internationalization. Finally, the universities in both the Netherlands and Finland are increasingly autonomous, though the journey towards autonomy has started later in Finnish universities compared to the Dutch universities.
Keywords: Hybridity; public sector; private sector; Universities; Governance; Structure; Finland; and the Netherlands; fi=Julkisjohtaminen|en=Public Management |; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|